Traumatic Ulcers in a Patient Using Fixed Orthodontic Appliances with Moderate Oral Hygiene - Kharinna Widowati; Nafiah Nafiah; Amalia Amanda (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
Traumatic ulcer is one of the most common ulcerated lesions bought on by local factors. It is usually a single ulcer, but multiple ulcers can also be found in some cases. Local factors that can result in traumatic ulcers include mechanical, thermal, and chemical factors. The most frequent mechanical causes of traumatic ulcers include utilizing orthodontic appliances, which can result in mechanical trauma. This case report, therefore, aims to provide information about the oral management of mechanical traumatic ulcers in a patient using fixed orthodontic appliances with moderate oral hygiene. A 22-year-old woman with moderate oral hygiene came to Oral Medicine Department RSGM Nala Husada with complaints of multiple sores on her lower lip, which was painful. Multiple ulcers (±10-15 mm), erythematous margin, and concave yellow base were visible on intra-oral examination. On the lower teeth around the lesions, there were fixed orthodontic appliances (only braces, no wire and power O/chain). As a pharmacological therapy, a triamcinolone acetonide was administered in addition to BecomC and antiseptic mouthwash. As a non-pharmacological therapy, patients have been educated about the importance of scaling and root planning and routine control of orthodontic appliances to eliminate local factors causing ulcers and improve oral hygiene. One week after removing the causative factor, the ulcer healed completely without scars or pain.